Convergences and Divergences in Career Paths: Recruiting Foreign Teachers in Binational Schools in Argentina - Mayer, Liliana Judith (2023)
This chapter seeks to analyze the reasons why binational schools house foreign native speakers’ teachers as part of their staff and the reasons that make foreign residents work in binational schools in Argentina. We developed a multiple case design to predict similarities or contrasts based on arguments that explain these differences (Yin, Case study research: design and methods. Sage, Thousand Oaks, 2003) and conducted 15 in-depth interviews with educational agents – teachers and authorities – from binational schools, between 2017 and 2020.Our findings show that divergences in ‘career paths’ are marked by different contracting mechanisms: while foreign teachers are recruited through specific net- works and enjoy economic privileges similar to diplomatic corps, Argentine teach- ers receive their salary in the local currency and according to national parameters. From these material advantages other symbolic ones will land. By creating a sense of belonging to an endogroup, some foreign teachers have the power to set the val- ues and identities that create meaning within the school. This ‘minority though elite’ group of teachers finds a fertile soil in the school ethos of binational schools, closely in line with cultural diplomacy. We conclude that binational schools tend to legitimate their added value through the hiring of foreign teachers, and foreign teachers find solid ground for a successful career path, granted by their place of birth, and by the credentials derived from educational paths that have proved to be advantageous for specific institutional projects.